2013
DOI: 10.1128/aac.01264-12
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into the Subclass B3 Metallo-β-Lactamase SMB-1 and the Mode of Inhibition by the Common Metallo-β-Lactamase Inhibitor Mercaptoacetate

Abstract: A novel subclass B3 metallo-␤-lactamase (MBL), SMB-1, recently identified from a Serratia marcescens clinical isolate, showed a higher hydrolytic activity against a wide range of ␤-lactams than did the other subclass B3 MBLs, i.e., BJP-1 and FEZ-1, from environmental bacteria. To identify the mechanism underlying the differences in substrate specificity among the subclass B3 MBLs, we determined the structure of SMB-1, using 1.6-Å diffraction data. Consequently, we found that SMB-1 reserves a space in the activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
67
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 49 publications
4
67
0
Order By: Relevance
“…As already described for the MBL fold (1-6), the whole domain of GOB-18 can be depicted as a duplication of two structurally similar ␣/␤ hemidomains. GOB-18 is very similar to other B3 lactamases (20)(21)(22)(23)(24), despite low sequence identity. Structural alignment of GOB-18 (chain A) with available B3 lactamase models allows for similarity quantification (Fig.…”
Section: Expression and Purification Of Gob-18 For Crystallogenesismentioning
confidence: 93%
See 3 more Smart Citations
“…As already described for the MBL fold (1-6), the whole domain of GOB-18 can be depicted as a duplication of two structurally similar ␣/␤ hemidomains. GOB-18 is very similar to other B3 lactamases (20)(21)(22)(23)(24), despite low sequence identity. Structural alignment of GOB-18 (chain A) with available B3 lactamase models allows for similarity quantification (Fig.…”
Section: Expression and Purification Of Gob-18 For Crystallogenesismentioning
confidence: 93%
“…All B3 lactamases crystallized so far are characterized by at least one disulfide bridge, in most cases between Cys residues located in the C-terminal helix and the loop linking elements ␣5 and ␤12 (20)(21)(22)(23)(24). GOB-18 is an exception in this regard within B3 enzymes, with only one Cys residue in its primary structure, i.e., Cys180 (201) (in strand ␤10), which is buried within the protein core (Fig.…”
Section: Expression and Purification Of Gob-18 For Crystallogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of techniques have already been developed to detect MBL producers (4), including a disk-based synergy test, the sodium mercaptoacetate (SMA) test, which is conventionally used in Japanese clinical microbiology laboratories (5). This test uses a Kirby-Bauer (KB) disk containing a b-lactam antibiotic (ceftazidime [CAZ] recommended) and a disk containing SMA, an MBL inhibitor that can bind to the MBL active site through interactions with zinc ions (6). Although this test works well for the detection of IMPand VIM-type MBL producers, which are the predominant MBL types in Japan (7), preliminary results have indicated that it may fail to detect NDM-1 producers when using the SMA test with the CAZ disk according to general recommendations (8).…”
mentioning
confidence: 99%